BO’LAJAK MUSIQA O’QITUVCHILARINI XOR DIRIJORLIGI FAOLIYATIGA TAYYORLASH MUAMMOLARI - Xodjayev, J.A. (SCIENCE and SOCIETY, 2023)
One of the unique important features of the training sessions of the subjects related to practical performance in the music specialty of the higher pedagogical education is that in addition to the tasks aimed at acquiring special competences in the subject, students are taught to independently apply them in practical activities. it is also required to acquire creative performance skills. This is especially true for students in choir performance, which is the most important part of the school's activities
Keywords: conducting art; conductor; conducting science; higher education; school music education; pedagogical activity of a music teacher; future music teacher; musical art